Listening to Music “in” the Library - Johnston, Lucinda (CAML Review / Revue de l’ACBM, 2020)
Digital and streaming audio and video (A/V) content have usurped the primacy of physical media materials and their playback technology within institutional music libraries, notwithstanding throwbacks to and resurgences of physical media in commercial and personal contexts. Music libraries are challenged with the conflicting responsibilities of maintaining legacy format materials that are not digitally available, continuing to collect physical resources that are not available either digitally or through institutional streaming subscriptions, and acquiring born-digital and digitized resources. They must also reconcile these responsibilities with the fact that many streaming A/V resources are freely available to individual consumers. In an era of dwindling resources and appreciation for curated music collections, how will libraries ensure that their A/V resources, in all formats, remain relevant to current and future users? This paper presents the results of an A/V usage survey administered to affiliates of the University of Alberta’s Music Department to learn about the attitudes, preferences and experiences of music library users’ practises for accessing recorded music.